Application of active query languages to the implementation of business rules - Vasilecas, Olegas; Saulis, Algis; Sinkevičius, Valdas; Dereškevičius, Saulius; Vaičiulis, Rimgaudas Stanislovas (Lietuvos matematikos rinkinys, 2004)
The paper deals with the problems of business rules implementation into the Web-based document management system. XML document storing, retrieving, querying, and transformation methods are analyzed. Different active methods based on ECA (event–condition–action) model have been discussed. An Active XQuery language is recognized as the most promising, but it lacks implementation means. A specialized XML extension is created and corresponding interpreter is developed to implement business rules into the document management system of the project MOCURIS. The method proposed can be used to solve similar tasks.